Computational Methods for Approximation of Large-Scale Descriptor Systems - Uddin, Mohammad Monir (Boca Raton, FL : CRC Press, 2018)
"This book mainly focuses on MOR techniques for the first and second order descriptor systems. The book also provides mathematical algorithms for implementing them in real-world applications. This book is intended for assisting undergraduates, graduates and researchers in academics and industries."--Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Approximation theory -- Data processing; Mathematics; Computer science; MATHEMATICS / General; TECHNOLOGY / Electricity